Single injection protocol for coronary and lower extremity CT angiographies in patients suspected for peripheral arterial disease. Issue 46 (November 2016) - Khandelwal, Ashish; Kondo, Takeshi; Amanuma, Makoto; Oida, Akitsugu; Sano, Tomonari; Sachin, Saboo S.; Takase, Shinichi; Rybicki, Frank J.; Kumamaru, Kanako K.
Abstract : Abstract: To evaluate the feasibility of a single injection protocol for coronary CT angiography (CTA) and lower extremity CTA in patients suspected for peripheral arterial disease (PAD). This prospective observational study included a total of 103 patients who showed an ankle brachial index ≤0.9 and underwent the single injection protocol for coronary and lower extremity CTA. All CTAs used iodinated contrast (weight × 0.06 mL/s × 20 seconds). A prospective Electrocardiogram (ECG)-gated coronary CTA was performed, followed by helical lower extremity CTA beginning 9 seconds after coronary CTA. Using catheter angiography as reference standard, diagnostic ability of CTA was evaluated. The mean total volume of iodinated contrast used was 70 ± 14 mL. Contrast opacification in the superficial femoral artery was adequate (408 ± 97 Hounsfield Units [HU]) and PAD was detected in 72.8% (75/103). The estimated radiation doses for lower extremity and coronary CTA were 3.6 ± 1.2 and 5.5 ± 4.5 mSv. A significant coronary stenosis was detected in 47 patients (45.6%). Coronary CT image quality was recorded as excellent in 86.4%, acceptable in 11.7%, and unacceptable for 1.9%. Contrast opacification within the superficial femoral artery was adequate in all cases while 27.2% needed an additional scan below the calf to capture the contrast bolus arrival in the smaller lower extremity vessels. Segment based sensitivity, specificity, positive, and negative predictive values were 57.9%, 97.9%, 73.8%, and 95.9% for the coronary CTA, and 63.4%, 91.5%, 76.3%, and 85.3% for peripheral CTA. A single injection protocol for coronary CTA and lower extremity CTA is feasible with a relatively small volume of iodinated contrast.